If it's not what You are looking for type in the equation solver your own equation and let us solve it.
h+1=7
We simplify the equation to the form, which is simple to understand
h+1=7
We move all terms containing h to the left and all other terms to the right.
+1h=+7-1
We simplify left and right side of the equation.
+1h=+6
We divide both sides of the equation by 1 to get h.
h=6
| x^2-11xy+24y^2=0 | | 1/3(5x-9)=7 | | 2(3x-3)=24 | | 12x^3-15x^2+4x-5=0 | | 4n-17=3+8n | | 9(x+3)=36 | | 39x=33x-78 | | 2s-25=3+9s | | 12x^3-9x^2-4x-3=0 | | 23-V=218 | | 60x^3+36x^2+3x=0 | | 9/7t=8 | | -6x+8y=8 | | 6g-9=15 | | 10x-5x=5045 | | -x^3+(6x^2)-9x+3=0 | | 9x-3=5x+17 | | -3x^2+2x+21=0 | | n^2+10n-119=0 | | 7x-4x=36393 | | 0=8x+9 | | 10x^2-11x+4=0 | | 4x/5=11 | | 5(y-15)=30 | | 3x+3x=61236 | | X-9/2=8 | | -44t^4+51t^3+5t^2=0 | | 3x+x+x-10=45 | | 799+25x=1000 | | 5(x+5)-5x(5-7x)= | | 26+-15+35= | | 9x+x=600 |